Geological and archaeological heritage in the Mediterranean coasts: Proposal and quantitative assessment of new geosites in SW Sardinia (Italy) - Fancello, D.; Columbu, S.; Cruciani, G.; Dulcetta, L.; Franceschelli, M. (Frontiers in Earth Science, 2022)
The south-western Sardinian coast (Italy), in the sector between the small village of Chia (Domus de Maria) and the Piscinnì locality (Teulada), is one of the most interesting of the island, being characterized by a wide geodiversity, a complex history testified by several archaeological sites, rich ecosystems and beautiful landscapes. This area is already famous as a seaside resort but its rich geological heritage it totally unrecognized and the educational and touristic potential of its archaeological sites is widely undervalued. In this paper we propose an itinerary in seven stages, each of which selected considering mainly its geology (geodiversity, scientific relevance of the geological features and educational potential), and also the additional values as the presence of archaeological sites and/or of ecological diversity and/or touristic attractions. The study area is described from geological and archaeological points of view, after a detailed field survey, the petrographic characterization of the main rocks, and an overview of the scientific literature. The quantitative assessment of the geosites values has been also performed, revealing a high potential for scientific, educational, and touristic purposes. The site-by-site description is reported in an appendix to be used as a field guide. The aim of this work is to propose the study area as a geotrail since it represents a valuable geological (and not only) heritage, to be protected, preserved, and valorised in the broadest meaning of the word. The main concerns related to the preservation and valorisation of this geosite are also addressed. Finally, a discussion on the geosite assessment methods is proposed to contribute to the scientific literature on geoheritage.